PENGARUH MARKETING MIX TERHADAP KEPUASAN PELANGGAN WARNET PADA WARNET BLASTNET DI PURWOREJO - Damar Eko Cahyono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This research was carried out had a purpose to test: 1) the Product towards the customer's satisfaction, 2) the Price towards the customer's satisfaction, 3) the Place towards the customer's satisfaction, 4) the Promotion towards satisfaction, 5) the Employee towards the customer's satisfaction, 6) the Process towards the customer's Satisfaction, 7) the Fisik Environment towards the customer's satisfaction. The data was gathered from 60 respondents by using the taking method random sampling. The analysis of the data was carried out through the analysis of the instrument of the research that covered the validity test used the correlation product moment and the test reliabilitas used the Cronbachs alpha; the hypothetical test used the analysis technique of linear regression. Results of this research showed that: 1) the Product towards the customer's satisfaction was influential positive and significant, meaning that increasingly fast access then the customer's satisfaction increasingly increased (the hypothesis was proven), 2) the Price towards the customer's satisfaction was influential positive and significant, meaning that increasingly cheap the price then the customer's satisfaction increasingly increased (the hypothesis was proven), 3) the Place towards the customer's satisfaction was influential positive and significant, meaning that increasingly stategis warnet then the customer would increasingly the customer's satisfaction increasingly increased (the hypothesis was proven), 4) the Promotion towards the customer's satisfaction was influential positive and significant, meaning that increasingly often carried out the program promo then the customer's satisfaction increasingly increased (the hypothesis was proven), 5) People towards the customer's satisfaction was influential the negative and significant, meaning that friendly and well-mannered the operator then the customer's satisfaction increasingly increased (the hypothesis was proven), 6) the Process towards the customer's satisfaction was influential the negative and significant, meaning that even more benefits that could be received by the customer then the customer's satisfaction increasingly increased (the hypothesis was proven), 7) the physical Environment towards the customer's satisfaction was influential positive and significant, meaning that increasingly complete facilities then the customer's satisfaction increasingly increased (the hypothesis was proven).